Characterization of gut microbiota in Vietnamese children under 5 years of age with acute and persistent diarrhea - Nghi Huu Chung; Tuan Anh Nguyen; Van Hung Pham; Luan Thanh Nguyen; Nhan Trong Phan; Chuyen Quoc Vo; Nguyen Thanh Nhu (Medicine, 2026)
Gut microbiota alterations have been increasingly associated with diarrheal diseases, a leading cause of morbidity and mortality in children under 5 years of age. However, explorations examining microbiota profiles across different diarrhea durations remain limited. Our study investigated microbiota alterations in Vietnamese children with diarrhea. We recruited 97 children under 5 years of age and divided them into 3 groups: healthy children (HC; n = 48), children with acute diarrhea (AD; n = 32), and children with persistent diarrhea (PD; n = 17). We collected and analyzed stool samples using 16S rRNA gene sequencing targeting the V3 to V4 region. Taxonomic classification was performed. Alpha diversity and beta diversity metrics were estimated. LEfSe analysis identified differentially abundant bacterial taxa across groups. Gut microbiota composition and diversity differed significantly among HC, AD, and PD. Alpha diversity tended to decline from HC to AD and was lowest in PD, with significant reductions observed for the Shannon index and Faith PD. Compared with HC, AD showed enrichment of Actinobacteriota and potentially pathogenic genera, including Streptococcus and Escherichia–Shigella , together with depletion of beneficial commensal taxa. PD exhibited more pronounced dysbiosis, including expansion of Proteobacteria, depletion of Bacteroidota-associated commensals, and a significantly reduced Bacteroidota-to-Firmicutes ratio. Children with AD and PD exhibited distinct gut microbiota alterations, with more pronounced microbial dysbiosis observed in PD. These findings improve our understanding of gut microbiota alterations associated with pediatric diarrhea and support future longitudinal studies incorporating comprehensive pathogen identification to clarify temporal relationships, evaluate microbiome-based biomarkers, and explore microbiota-targeted interventions.